Kurdistan Natural Asphalt as Paving & Mastic Asphalt Compared with Petroleum Base Asphalt - Karim, Abdul-Salam Rahim (Sulaimani Journal for Pure and Applied Sciences, 1999)
The bituminous material of kurdistan has been studied for using it as paving, mastic, and water proofing asphalt. The results showed that after treatment with water motor oil or atmospheric distillation residue produced in Kurdistan refinery. It was possible to produce base asphalt of different penetration grades between 40 to 300 in the ratios of 25, 35 and 50% w/w bitumen within the international specifications, except ductility which can be achieved also by rasing temp. of petroleum distillation up to 360 0c. Asphalt paving mixtures have been prepared using the local base asphalt of (40-50) penetration grade and mineral filler and fine aggregates according to AASHTO specifications using different asphalt ratios namely (4,4.5 and 5% w/w) with requirements of Marshall and deforming tests and compared with asphalt paving mixtures petroleum base asphalt produced in Baiji refinery, these laboratory works improved by plant application by paving (52) m of Sulaimany-Arbat road. Then mastic asphalt according to the specifications ASTM D491-79 was prepared by mixing filler and aggregates with the locally prepared base asphalt in the following ratios (base asphalt 30% filler 30% fine aggregate 30% coarse aggregate 10% 2) by using four different fillers, namely (cement, sand, active clay, and sulfur) and all results compared with those obtained from mastic asphalt prepared using petroleum base asphalt produced in Baiji refinery.